Development of antibiotic resistance genes in microbial communities during long-term operation of anaerobic reactors in the treatment of pharmaceutical wastewater. (15th October 2015) - Aydin, Sevcan; Ince, Bahar; Ince, Orhan
Abstract: Biological treatment processes offer the ideal conditions in which a high diversity of microorganisms can grow and develop. The wastewater produced during these processes is contaminated with antibiotics and, as such, they provide the ideal setting for the acquisition and proliferation of antibiotic resistance genes (ARGs). This research investigated the occurrence and variation in the ARGs found during the one-year operation of the anaerobic sequencing batch reactors (SBRs) used to treat pharmaceutical wastewater that contained combinations of sulfamethoxazole-tetracycline-erythromycin (STE) and sulfamethoxazole-tetracycline (ST). The existence of eighteen ARGs encoding resistance to sulfamethoxazole ( sul1, sul2, sul3 ), erythromycin ( ermA, ermF, ermB, msrA, ereA ), tetracycline ( tetA, tetB, tetC, tetD, tetE, tetM, tetS, tetQ, tetW, tetX ) and class Ι integron gene ( intΙ 1 ) in the STE and ST reactors was investigated by quantitative real-time PCR. Due to the limited availability of primers to detect ARGs, Illumina sequencing was also performed on the sludge and effluent of the STE and ST reactors. Although there was good reactor performance in the SBRs, which corresponds to min 80% COD removal efficiency, tetA, tetB, sul1, sul2 and ermB genes were among those ARGs detected in the effluent from STE and ST reactors. A comparison of the ARGs acquired from the STE and ST reactors revealed that the effluent from the STE reactor had a higher number of ARGs than that from the ST reactor; this could be due to the synergistic effects of erythromycin. According to the expression of genes results, microorganisms achieve tetracycline and erythromycin resistance through a combination of three mechanisms: efflux pumping protein, modification of the antibiotic target and modifying enzymes. There was also a significant association between the presence of the class 1 integron and sulfamethoxazole resistance genes. Graphical abstract: Highlights: We examine triple and dual effects of antibiotics on emergence of antibiotic resistance throughout a year operation. Triple effects of antibiotic are much more greater than dual effects due to proliferation of antibiotic resistance genes. Sulfamethoxazole, tetracycline and erythromycin resistance genes increased with increasing antibiotic concentration.